Infant Feeding Practices among Mothers with a History of Gestational Diabetes Mellitus in Selangor - Ramlee, Nur Syafika; Abdul Hamid, Syahrul Bariah; Ahmad Shuhaimi, Farhanah (Jurnal Gizi dan Pangan, 2024)
This study aims to determine infant feeding practices including breastfeeding initiation, exclusive breastfeeding, duration of breastfeeding and complementary feeding, feeding practices related factors among mothers with Gestational Diabetes Mellitus (GDM) history, and the association between Infant and Young Child Feeding indicators and GDM status. A cross-sectional study (n=130) was conducted from February to June 2023 in Meru and Bandar Botanic health clinics. Data on infant feeding practices were gathered from GDM mothers and children aged below two years. Findings showed that 43.8% (n=57) of the mothers had initiated breastfeeding within an hour, 57.7% (n=75) infants were exclusively breastfed, 30.0% (n=39) continued breastfeeding for one year and 81.9% (n=68) had an appropriate time of complementary feeding. Mothers who had caesarean-section delivery and GDM were more likely to initiate breastfeeding after an hour of delivery, p<0.05. Exclusive breastfeeding was highly practiced by older, multiparous, and higher education mothers. Unemployed mothers were more likely to continue breastfeeding for one year. GDM mothers were more inclined to delay breastfeeding initiation and introduced complementary feeding appropriately, p<0.05. This study's findings bridge the gap in providing information on infant feeding practices among mothers with a history of GDM and therefore might be beneficial for related personnel to figure out how to overcome this concerning issue in the future.